Performance study of streaming services over all-IP wireless networks - ZHAO Hai-bo; LUO Xing-guo; TANG Xiao-mei (Tongxin xuebao)
An end-to-end quality of service（QoS） analytic method for streaming media over an ALL-IP wireless network was proposed,which was applicable to analyze the cumulative performance degradation along the service architecture based on a bottom-up approach.The radio interface of wireless network consisted of a variable-rate multi-user and multi-channel subsystem.By means of both mathematic analysis and simulations,three QoS attributes were evaluated: delay,throughput and loss rate.